Metabolic fate of tea polyphenols and their crosstalk with gut microbiota - Meiyan Wang; Jianying Li; Ting Hu; Hui Zhao (Food Science and Human Wellness)
Tea represents an abundant source of naturally occurring polyphenols. Tea polyphenols (TPs) have received growing attentions for its wide consumption in the world, and more importantly its pleiotropic bioeffects for human health. After ingestion, TPs may undergo absorption and phase II reaction in the small intestine, and most undigested proportion would be submitted to the colon to interact with gut microbiota. Interactions between gut microbiota and TPs are bidirectional, including not only bacteria-mediated TPs metabolism, e.g., removal of gallic acid moiety and ring fission to release phenolic acid catabolites, but also TPs-based modification of bacterial profiles. Crosstalk between TPs and gut microbes may benefit for gut barrier function, for example, improvement of the intestinal permeability to alleviate inflammation. Moreover, by reshaping microbial composition and associated metabolites, TPs may exert a systemic protection on host metabolism, which contributes to improve certain chronic metabolic disorders. Given that, further understanding of the metabolic fate of TPs and interplay with gut microbiota as well as potential health-promoting effects are of great significance to development and application of tea and their polyphenolic components in the future as dietary supplements and/or functional ingredients in medical foods.